The role of digital branding on consumer retention: evaluating uses of social media in Bangladesh - Priyanka, Afsary Adiba (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.